‘Singing the Lord’s Song in a Strange Land’: A ‘Bio-Ethnography’ of Christianity and Genetic Engineering in Scotland - Watling, Tony (Journal for the study of religion, nature and culture, 2006)
Genetic engineering is at the forefront of scientific thought and practice. It has immense implications economically, environmentally, politically, and socially, questioning what we know as ‘life’, ‘nature’, and ‘humanity’, and possibly reframing human interaction with nature. Because of this it leads science and government into the realm of ethics. The latter has traditionally been seen to be the domain of religion, often seen as lacking relevance in today’s ‘modern’ world that has fragmented frameworks that previously supported or controlled individuals. However, the instability and isolation from ethical resources this creates may provide problems when dealing with challenging issues—such as genetic engineering—suggesting the need for ethical guidelines and support something that religion provides. The aim of this article, therefore, is to provide a qualitative understanding—a ‘Bio-Ethnography’—of how religious believers, in particular Church of Scotland Christians, perceive and experience genetic engineering highlighting the personal, social, and environmental, issues it raises, and exploring Christian understandings and negotiation of them.